Evaluating the impact of smoking on disease‐specific survival outcomes in patients with human papillomavirus–associated oropharyngeal cancer treated with transoral robotic surgery. Issue 9 (7th February 2020) - Roden, Dylan F.; Hobelmann, Kealan; Vimawala, Swar; Richa, Tony; Fundakowski, Christopher E.; Goldman, Richard; Luginbuhl, Adam; Curry, Joseph M.; Cognetti, David M.
Abstract : Background: When treated nonsurgically with definitive chemoradiation, smokers with human papillomavirus (HPV)–positive oropharyngeal squamous cell carcinoma (OPSCC) have a worse prognosis compared with their nonsmoking counterparts. To the authors' knowledge, the prognostic significance of smoking in surgically treated patients is unknown. Methods: The current study is a retrospective case series of patients with HPV‐positive OPSCC who underwent upfront transoral robotic surgery at a single institution from 2010 through 2017. Exclusion criteria were nonoropharyngeal primary tumors, histology other than SCC, HPV‐negative tumors, previous history of head and neck cancer, and/or previous head and neck radiotherapy. Recurrence‐free survival (RFS), overall survival, and disease‐specific survival were compared using the Kaplan‐Meier method and the log‐rank test. Smoking history was categorized as never smokers (<1 pack‐year), current smokers (smoking at the time of the cancer diagnosis), and former smokers. Results: A total of 258 patients met the study criteria. The average age was 60 years, and approximately 87% of patients were male. A total of 148 patients (57.4%) were smokers whereas 110 (42.6%) reported never smoking. There were 44 active smokers (17.1%) and 104 former smokers (40.3%). The median follow‐up was 3.23 years. There were 17 patients of disease recurrence. Smoking pack‐year history was not found to be significant for RFS (hazard ratio, 1.01; 95% CI, 0.99‐1.03 [ P  = .45]). There was no significant difference in RFS noted between never and ever smokers (92% vs 89.8%; P  = .85) nor was there a difference observed between never, former, and current smokers (92% vs 91.5% vs 86.1%, respectively; P  = .69). Conclusions: A smoking history is common in patients with HPV‐positive OPSCC. In the current study, HPV‐positive smokers were found to have excellent survival and locoregional control, similar to their nonsmoking counterparts. The results of the current study do not support the exclusion of smokers with early‐stage, HPV‐positive OPSCC from transoral robotic surgery–based deintensification trials. Abstract : Contrary to what has been published in the literature regarding the negative prognostic impact of smoking on survival outcomes among patients with human papillomavirus (HPV)–positive oropharyngeal squamous cell carcinoma (OPSCC) who are treated with nonsurgical definitive therapy, smoking does not appear to significantly impact recurrence‐free survival in patients with HPV‐positive OPSCC who are treated with upfront transoral robotic surgery (TORS) followed by pathology‐directed adjuvant therapy. These data do not support the exclusion of smokers from prospective TORS‐based deintensification trials.